Gestural and Prosodic Development Act as Sister Systems and Jointly Pave the Way for Children’s Sociopragmatic Development - Hübscher, Iris; Prieto, Pilar (Frontiers in Psychology, 2019)
Children might combine gesture and prosody to express a pragmatic meaning such as a request, information focus, uncertainty or politeness, before they can convey these meanings in speech. However, little is known about the developmental trajectories of gestural and prosodic patterns and how they relate to a child’s growing understanding and propositional use of these sociopragmatic meanings. Do gesture and prosody act as sister systems in pragmatic development? Do children acquire these components of language before they are able to express themselves through spoken language, thus acting as forerunners children’s pragmatic development? This review article assesses empirical evidence that demonstrates that gesture and prosody act as intimately related systems and, importantly, pave the way for pragmatic acquisition at different developmental stages. The review goes on to explore how the integration of gesture and prosody with semantics and syntax can impact language acquisition and how multimodal interventions can be used effectively in educational settings. Our review findings support the importance of simultaneously assessing both the prosodic and the gestural components of language in the fields of language development, language learning, and language intervention.